Dendroclimatic potential of Pinus pinceana Gordon in the Sierra Madre Oriental - Santillán-Hernández, Miriam; Cornejo-Oviedo, Eladio H.; Villanueva-Díaz, José; Cerano-Paredes, Julián; Valencia-Manzo, Salvador; Capó-Arteaga, Miguel Ángel (Instituto de Ecología, A.C., 2016)
The climate sensitivity of ten populations of Pinus pinceana Gordon was determined to analyze their potential for climate reconstruction purposes. The P. pinceana populations are distributed along a latitudinal gradient of the Sierra Madre Oriental and for this study are considered as northeast region ( Zacatecas, Coahuila), north-central region (San Luis Potosi), and central region (Hidalgo, Queretaro ).All populations were dated to the year of the annual growth formation except a population called “El Arenalito” in the central region. The youngest trees were found at populations in the central region (MAG, TEP, and CRI); therefore short tree-ring chronologies were developed for these sites. In contrast, for the northeastern region the populations PAL and NOR had the oldest trees and longer chronologies were developed for these sites. Intercorrelation values (0,61 to 0,77), mean sensitivity (0,49 to 0,69), and sign-to noise ratio values (11,72 to 33,64) are considered high for dendrochronological purposes. The statistic parameters derived from the ARSTAN software indicated that P. pinceana is climate sensitive and shows a similar behavior to other conifer species currently used for dendroclimatic studies in northern Mexico. Response function analysis indicated that the populations located in the northeast and north-central regions significantly responded to the seasonal January-June precipitation (winter-spring seasons), but the central populations did not show a clear response. Defining patterns of reduced annual growth are basic to date this species.